Kontribusi Pasraman dalam Pelestarian Seni dan Kebudayaan Bagi Generasi Hindu Pada Era Disrupsi Pendidikan - Swana, I Putu; Dewi, Ni Luh Made Larasanthi Komala (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This study aims to analyse and find out the contribution of Paraman in preserving arts and culture for Hindu generations in the era of educational disruption. This study was conducted with a phenomenological approach to Pasraman in Mataram City, while the data collection method used observation, documentation interviews and literature studies which were analysed using a descriptive qualitative approach. The findings of this study are that Pasraman in Mataram City has an important role in the preservation of arts and culture, the formation of the LP3 organisation in Mataram City is used as a medium of communication and interculture between pasraman, as a bridge of communication and coordination with related stake holders and as a driver of activities that are able to revive the pasraman behind the onslaught of the era of educational disruption after the Covid 19 outbreak. The form of pasraman's contribution in preserving arts and culture for the Hindu generation in this era of disruption in education is the internalisation of Hindu arts and culture-based learning which includes (1) Performing Arts (Dance Training, Drumming and Dharmagita); (2) Fine Arts (Upakara Learning); (3) Recording Media Arts (Video Content Creation Training) and (4) Literary Arts (Learning to Write and Read Balinese Script).